(3GdbUjOI GdOGeZIs - (3GdMSf Hf CMeO Hf jYbhH GdgeOGfj , GHf GdMGFc , CHh eMeO,J (B334 (3g` s ((3Ydj Hf RjO Hf CMeO Hf ESMGb Hf jMji Hf CHj jMji s)
(3ChdgG (B:s
(3CeG HYO, CcQec Gddg HGdJbhi abO JCedJ cJGHc, hageJ eG PcQJ s
(3BNQgG (B:s
(3hEfi ef gePGf aj SQ SQgG Edi Bd YHO ef Hcjd hCOgeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdbUjOI CLGH HgG GdcejJ Hf RjO GdCSOj haSQgG hTQMgG CMO JdGejP GdgePGfjs
(3aj cTa GdXfhf hgOjI GdYGQajf Cf GdbUjOI aj GddZI hGdUMjM CfgG aj aVd bMWGfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B204 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B269s
Keywords: (3GdCOHs